El voto preferente como promotor de la personalización política en Colombia, a partir del A.L. 001 de 2003 (2022)
Legislative Act 001 of 2003, modified the electoral system in Colombia, generated changes such as the conversion of votes into seats, gave way to an excessive increase in political parties with varied interests in both public and private corporations, giving way to new warlordism , very different from those heroes who participated in the independence processes, the current ones become populist figures fed by ideologies that favor privileged sectors of the Colombian population, weakening the nature of the parties and the normal exercise of democracy. These personalisms have been placed above the ideology of the political institutions within which they militated; including, moving away from the programs established by their parties and replacing them with eminently populist and immediate actions, which has generated the denaturation of democracy, given the precariousness of political participation and the imposition of personalisms on ideologies. This corruption is generated because the necessary tools for democratization and transparency in the parties do not exist, creating the phenomenon of abstentionism due to acts of political corruption, divisions or polarization of opinion that occurs in many caudillos, among others. Separating participatory and representative democracy from the national and international environment due to the uncertainty and lack of trust of the people.